20veinte (2020)
One way of understanding the history of humanity is throughout the study of artistic movements that have defined and shaped the state of the art and the dogmatic affiliations of societies, especially in the West. The avant-gardes can be identified and distinguished, they are aesthetic proposals of a concrete character, differentiating within their context, which are welcomed in recognition or reaction to their context and the events that define the transition between one period and another. In this order of ideas, the 20veinte Manifesto is proposed, a Design project that seeks to take as a basis the responses from the field of Design to the needs of users in the context of the situation posed by the health emergency of COVID-19. The intention is to interpret the essence of these approaches and with this define new archetypes that build an emerging avant-garde for the third decade of the 21st century...